Optimizing formulation and synthesis conditions of red palm oil (RPO)-based nanoemulsions stabilized by tween 80 - Megat Nasir, Megat Taufiq; Nasaruddin, Ricca Rahman; Mansor, Mariatul Fadzillah (IIUM Press, 2025)
Nanoemulsion is an important class of nanomaterial that offers several advantages due to its improved stability and dispersibility in aqueous systems. In this preliminary study, oil-in-water nanoemulsions were synthesized using red palm oil (RPO). RPO was chosen for its high insoluble vitamin E content, a potent antioxidant that can reduce oxidative stress by neutralizing free radicals. The most suitable emulsifier, optimal formulation, and synthesis conditions to produce stable nanoemulsions were evaluated. A laser beam penetration test based on the Tyndall effect and light-scattering principles was used to confirm the presence of nanoemulsions qualitatively. The results indicate that Tween-80 produced the most stable and translucent nanoemulsion. The optimal formulation was found to have a weight ratio of 10:15:74:1 for RPO: Tween 80: water: glycerin. The optimal synthesis conditions were using the high-speed homogenizer at 15000 rpm for 40-minute synthesis time. The resulting nanoemulsions demonstrated stability suitable for further studies (e.g., physicochemical characterization, scale-up, and additional functionalization) for food and beverage applications